Analysis of Soil Properties Variations on Various Slope Directions on the National Vegetation Ecosystem of Mount Ciremai, West Java - Agus Yadi Ismail; Cecep Kusmana; Eming Sudiana; Sukron Aminudin; Mai Fernando Nainggolan (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Mount Ciremai National Park has an area of ±15,500 ha with soil characteristics at various heights and varied slope directions. This study aims to determine the characteristics of soil properties in Gunung Ciremai National Park based on slope direction and its relationship with vegetation growth. The method used in this study is a systematic sampling method based on height intervals on four slopes with depths of 0-15 cm and 16-30 cm. The results showed 1). Soil pH in all four slopes with different heights in the acid-neutral category, 2). The soil texture is classified as sandy-loam and sandy-clay loam, 3). C-organic content is classified as low-very high, 4). The content of N-Total is classified as low-high. 5). P2O5 content is classified as very low-low, 6). K content is classified as low-very high, 7). Ca content is low-very high, and 8). Mg content is classified as low to high. Significant correlation tests of soil physical and chemical properties are found on several parameters such as C/N ratio, K, and Mg.